The ECB's New Multi-Country Model for the euro area: NMCM - simulated with rational expectations - Alistair Dieppe; Alberto González Pandiella; Alpo Willman (European Central Bank (ECB), 2011)
The model presented here is a New estimated medium-scale Multi-Country Model (NMCM) which covers the five largest euro area countries and is used for forecasting and scenarios analysis at the European Central Bank. The model has a tight theoretical structure which allows for non-unitary elasticity of substitution, non-constant augmenting technical progress and heterogeneous sectors with differentiated price and income elastiticites of demand across sectors. Furthermore, it has the explicit inclusion of expectations on the basis of three optimising private sector decision making units: i.e. firms, trade unions and households, where output is in the short run demand-determined and monopolistically competing firms set prices and factor demands. Labour is indivisible and monopoly-unions set wages and households make consumption/saving decisions. We assume agents optimise under limited information where each agent knows only the parameters related to his/her optimization problem. Therefore we estimate with GMM, which implicitly assumes limited information boundedly rational expectations. In this paper we provide some simulation results under the assumption of model-consistent rational expectations, we show that there is some heterogeneity across countries and that the reactions of the economies to shocks depends strongly on whether the shocks are pre-announced, announced and credible or unannounced and uncredible.
Keywords: C51; C6; E5; 330; Macro model; open-economy macroeconomics; Rational Expectations